Teori Penjaminan Simpanan Perbankan: Sebuah Intisari - Wardhana, Leo Indra; Sufitri, Sufitri (Faculty of Economics and Business Universitas Jenderal Soedirman, 2019)
This article summarizes the two main theories of deposit insurance, i.e. Diamond and Dybvig (1984) and Keraken and Wallace (1978), as well as discussing how the system is implemented in Indonesia and ASEAN countries. The article aims to give a simple yet comprehensive understanding for banking and finance students on two main theoretical papers in banking, both for under- and postgraduate students.